Smart City EU - Lighthouse Projects – Investigation of Economic Benefits (European Journal of Marketing and Economics, 2021)
The major European Smart City Lighthouse Projects have gained a lot of attention and importance from the designers of Smart City Initiatives (SCI) since 2014. The EU Commission's funding under the Horizon 2020 program is significant. The supported cities include the European metropolises but also several smaller cities. All these cities are repeatedly named Smart City pioneers. However, the research still has a gap when it comes to value generation. This article deals with the economic benefits of these Lighthouse projects. The own developed categories are applied and proved with Lighthouse projects. The range of economic benefits is shown and evaluated using the qualitative content analysis of the data from the EU - CORDIS database. The sustainability in the Smart City Initiatives is showcased as economic benefit is prioritized higher than cost saving or efficiency.
Keywords: Smart City, Economic Benefits, Urban Studies, Sustainability, Lighthouse Projects, EU – Programs